2018
DOI: 10.1038/s41416-018-0183-x
|View full text |Cite
|
Sign up to set email alerts
|

Routine blood investigations have limited utility in surveillance of aggressive lymphoma in asymptomatic patients in complete remission

Abstract: Routine blood tests demonstrate unacceptably poor performance characteristics, have no impact on survival and thus have limited value in the detection of relapse in routine surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…Another practice of limited evidence in detecting relapse is the performance of regular blood testing in the surveillance of DLBCL [20]. Recently, Hawkes and cols have shown that blood tests do not reliably detect relapse in asymptomatic patients with aggressive lymphoma in CR [21]. In our study, we only detected one patient in which relapse was suspected by abnormal blood test either with physical examination abnormality.…”
Section: Discussionmentioning
confidence: 71%
“…Another practice of limited evidence in detecting relapse is the performance of regular blood testing in the surveillance of DLBCL [20]. Recently, Hawkes and cols have shown that blood tests do not reliably detect relapse in asymptomatic patients with aggressive lymphoma in CR [21]. In our study, we only detected one patient in which relapse was suspected by abnormal blood test either with physical examination abnormality.…”
Section: Discussionmentioning
confidence: 71%
“…This result was in line with that of a previous study of aggressive lymphoma in which routine blood tests did not reliably detect relapse in asymptomatic patients (only 5% of relapse cases were detected) and had no impact on survival. 27 These results suggest that routine blood tests, similar to routine surveillance CT, may have limited value in the detection of lymphoma relapse.…”
Section: Discussionmentioning
confidence: 96%
“…Blood routine test contributes to controlling the occurrence and changes of diseases in the body in time (Hawkes et al. 2018 ). D -Xylose, a kind of pentose, is absorbed in the small intestine after oral administration, which reflects the absorption function of the small intestine (Rubino et al.…”
Section: Discussionmentioning
confidence: 99%